Comparison of plasma, venous and capillary blood levels of piperaquine in patients with uncomplicated falciparum malaria - Ashley, E; Stepniewska, K; Lindegardh, N; Annerberg, A; Tarning, J; McGready, R; Phaiphun, L; Singhasivanon, P; White, N; Nosten, F (2010)
Purpose Dihydroartemisinin-piperaquine (DP) is a fixeddose artemisinin-based combination treatment. Field pharmacokinetic studies would be simplified and facilitated by being able to use small volume capillary assays rather than venous blood. The aim of this study was to describe the relationship between piperaquine concentrations measured in capillary blood, venous blood and venous plasma. Methods Samples of plasma, whole blood obtained by venesection and capillary blood were taken simultaneously from patients with uncomplicated Plasmodium falciparum malaria treated with DP between 0 and 9 weeks after treatment. Piperaquine concentrations in venous and capillary samples were measured using solid phase extraction and analysis by liquid chromatography with ultraviolet detection. Results A total of 161 sets of the three measures were obtained from 54 patients. Piperaquine concentrations in the venous blood samples were approximately twofold higher and those in the capillary blood samples were threefold higher than the corresponding venous plasma concentrations. Capillary blood piperaquine concentrations were approximately 1.7-fold higher than venous blood concentrations, and this difference also increased with time. Conclusion Differences in whole blood and plasma levels of piperaquine suggest compartmentalisation of the drug within blood cells, as also occurs with the structurally related quinoline chloroquine. The relationship between piperaquine concentrations in the venous plasma, venous blood and capillary blood is variable and unpredictable at low concentrations. However, within the range of concentrations usually present in patients between 3 and 21 days after treatment with currently recommended doses, the relationship between capillary and venous whole blood is predictable; consequently, capillary blood sampling can be used in field assessments.